Group Policy : Fundamentals, Security, and the Managed Desktop. - Moskowitz, Jeremy (John Wiley & Sons, 2010)
The ultimate Group Policy guide-now updated for Windows 7 and Server 2008 R2!. IT and network administrators can streamline their Windows Server management tasks by using Group Policy tools to automate or implement rules, processes, or new security across the enterprise. In this comprehensive guide, Microsoft Group Policy MVP Jeremy Moskowitz thoroughly explores Group Policy across all Windows platforms, including the latest on Windows 7 and Server 2008 R2. If you're a Windows network administrator managing scores of users and computers, you need this essential reference on your desk.: Covers.